2003
DOI: 10.1177/0734242x0302100207
|View full text |Cite
|
Sign up to set email alerts
|

Determination of field capacity of municipal solid waste with surcharge simulation

Abstract: The following study was carried out as part of the environmental monitoring of a landfill in Nuevo Laredo, Tamaulipas (Mexico). The parameter of field capacity is important in predicting the amount of leachate generated by solid waste disposal sites, because of the polluting potential of leachate. This paper describes how the field capacity for municipal solid waste was determined, and the purpose of this document is to present a methodology, and to describe the devices designed for determining the field capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 5 publications
3
10
0
1
Order By: Relevance
“…13), which is in line with other modeling approaches (e.g., São Mateus et al 2012, Lobo et al 2002, Lobo and Tejero 2007, assumes that the waste field capacity decreases if the mean pressure on the waste, r s , increases because of the materials redistribution which entails voids reduction in number and size. This behavior was also observed in some laboratory tests carried out by Powrie et al (2000), De Velásquez et al (2003b), Olivier and Gourc (2007) and Wu et al (2012). However, it should be considered that this aspect is still under discussion.…”
Section: Incoming Watersupporting
confidence: 73%
“…13), which is in line with other modeling approaches (e.g., São Mateus et al 2012, Lobo et al 2002, Lobo and Tejero 2007, assumes that the waste field capacity decreases if the mean pressure on the waste, r s , increases because of the materials redistribution which entails voids reduction in number and size. This behavior was also observed in some laboratory tests carried out by Powrie et al (2000), De Velásquez et al (2003b), Olivier and Gourc (2007) and Wu et al (2012). However, it should be considered that this aspect is still under discussion.…”
Section: Incoming Watersupporting
confidence: 73%
“…Beaven (2000) investigated the hydrogeological properties of typical household waste in England contained in a large size compression cell (2 m in diameter), and found that the gravimetric water content at field capacity of the waste reduced with increasing waste density and stress. de Velásquez et al (2003) conducted field capacity tests on a typical Mexican MSW, and the results showed that the higher the compaction of the sample, the smaller the amount of water required to satisfy the field capacity and thus to start the leaching process. Tu et al (2008) carried out laboratory tests to measure water holdup on artificial waste typical to China, and showed that the gravimetric water holdup of the waste decreases with increasing dry density.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have identified the factors influencing the degradation of MSW and have assessed their individual effects on the methane production. These factors include presence or absence of oxygen and hydrogen [3][4][5]; temperature [6,7]; MSW confinement time [8]; MSW field capacity and hydraulic retention time [9][10][11]; compaction and compressibility of MSW [12]; pH [13,14]; type of material used as final cover layer and the codisposition of wastes from the construction and demolition industry [15,16]; humidity content and water flow [17,18] and; the use of inoculants such as biosolids and compost, and leachate recycling [19][20][21][22][23][24][25][26]. Although the aforementioned factors are interdependent, [27] identified pH and humidity content as being most critical, whereas [28] emphasized humidity and nutrient contents as the main factors affecting the stabilization of MSW.…”
Section: Introductionmentioning
confidence: 99%